2019
DOI: 10.1371/journal.pgen.1008057
|View full text |Cite
|
Sign up to set email alerts
|

Cellular response to small molecules that selectively stall protein synthesis by the ribosome

Abstract: Identifying small molecules that inhibit protein synthesis by selectively stalling the ribosome constitutes a new strategy for therapeutic development. Compounds that inhibit the translation of PCSK9, a major regulator of low-density lipoprotein cholesterol, have been identified that reduce LDL cholesterol in preclinical models and that affect the translation of only a few off-target proteins. Although some of these compounds hold potential for future therapeutic development, it is not known how they impact th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…We previously reported that an ortholog of yeast Slh1, ASCC3, is required for RQC 8 . In addition, a recent study suggested the involvement of ASCC3 and ASCC2 in co-translational quality control 20 . ASCC3 was originally identified as a component of the activating signal cointegrator 1 (ASC-1) complex, which consists of ASCC3, ASCC2, ASCC1, and TRIP4/ASC-1 (Fig.…”
Section: Analysis Of the Domains Of Znf598 Required For Rqc To Determentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that an ortholog of yeast Slh1, ASCC3, is required for RQC 8 . In addition, a recent study suggested the involvement of ASCC3 and ASCC2 in co-translational quality control 20 . ASCC3 was originally identified as a component of the activating signal cointegrator 1 (ASC-1) complex, which consists of ASCC3, ASCC2, ASCC1, and TRIP4/ASC-1 (Fig.…”
Section: Analysis Of the Domains Of Znf598 Required For Rqc To Determentioning
confidence: 99%
“…We previously reported that ASCC3 is required for RQC induction 8 . A recent study showed that ASCC2 and ASCC3 bind to the ribosome and mitigate the toxic effects of stalling induced by PF8503 20 . The ATP-dependent helicase ASCC3 is an ortholog of Slh1(Rqt2) 8 , and the ubiquitin-binding protein ASCC2 has significant sequence homology to yeast Cue3(Rqt3), implying the existence of a human RQT (hRQT) complex.…”
mentioning
confidence: 99%
“…In addition, ASCC3 has been implicated in viral defense mechanisms 18 21 . Finally, a genome-wide CRISPRi screen showed that ASCC2 and ASCC3 are the two most potent modifiers of cell fitness in the presence of a translation inhibitor, suggesting that the proteins affect stalled ribosomes 22 . Indeed, ASCC3 has been suggested to resolve stalled ribosomes on poly-A sequences in a ribosome quality control pathway 23 25 .…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the six CADs we screened vs. genome-scale screens (as opposed to targeted screens, e.g., involving the kinome) we and others performed with non-CADs shows the specificity of the CADs signature ( Figure 1C) (1)(2)(3)(4)(5). There were nineteen genes that scored on average an absolute value of at least 2.5 standard deviations away from the mean for the six CADs screens (hereafter referred to as pooled variance, PV) ( Figure 1C, Table S1).…”
mentioning
confidence: 99%